Grammatical errors in spoken english of University students in oral communication course - Su-Hie Ting,; Mahanita Mahadhir,; Siew-Lee Chang, (Penerbit UKM, 2010)
The present study examines the grammatical errors in spoken English of university students who are less proficient in English. The specific objectives of the study are to determine the types of errors and the changes in grammatical accuracy during the duration of the English for Social Purposes course focussing on oral communication. The language data were obtained from the simulated oral interactions of 42 students participating in five role play situations during the 14-week semester. Error analysis of 126 oral interactions showed that the five common grammar errors made by the learners are preposition, question, article, plural form of nouns, subject-verb agreement and tense. Based on Dulay, Burt and Krashen’s (1982) surface structure taxonomy, the main ways by which students modify the target forms are misinformation and omission, with addition of elements or misordering being less frequent. The results also showed an increase in grammatical accuracy in the students’ spoken English towards the end of the course.